KERAGAMAN FENOTIPE RAPD Santalum album L. DIPULAU TIMOR BAGIAN TIMUR - Yuyu S Poerba; Albert H Wawo; KS Yulita (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Santalum album L. (sandalwood/cendana) is known as one of medicinal and aromatic tree species in Indonesia. The species is valued for its quality light wood timber and for its medicinal properties.The species has been overexploited and is considered as vulnerable plant species.The present study aimed to assess genetic diversity and to estimate genetic relationship among 58 accessions of plant germplasm collection using Random Amplified Polymorphic DNA (RAPD).Two RAPD primers generated 34 scorable bands with 97.06% of them were polymorphic. Clustering analysis was performed based on RAPD profiles using the UPGMA method.The range of genetic dissimilarity value among species was from 6% to 91%, while the range of genetic distance between populations was from 1.89% and 26.88%.These values showed that 5.album from Eastern part of Timor was genetically diverse populations.Within the 12 populations, there were 9 banding patterns recorded from primer OPA 16 and 12 banding patterns from primer OPB 12, suggesting that OPB 12 was more sensitive than that of OPA 16 to show variation within the sample used.